2018
DOI: 10.3390/ijms19124122
|View full text |Cite
|
Sign up to set email alerts
|

S100A10 and Cancer Hallmarks: Structure, Functions, and its Emerging Role in Ovarian Cancer

Abstract: S100A10, which is also known as p11, is located in the plasma membrane and forms a heterotetramer with annexin A2. The heterotetramer, comprising of two subunits of annexin A2 and S100A10, activates the plasminogen activation pathway, which is involved in cellular repair of normal tissues. Increased expression of annexin A2 and S100A10 in cancer cells leads to increased levels of plasmin—which promotes the degradation of the extracellular matrix—increased angiogenesis, and the invasion of the surrounding organ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 114 publications
(173 reference statements)
1
27
0
Order By: Relevance
“…Although data from p11 KO-mice often supports findings that AnxA2/p11-dependent plasmin generation is involved in tumour progression [ 115 , 116 , 121 ], it should be noted that p11 has plenty of other tumourigenic functions that appear rather unrelated to AnxA2 [ 174 , 175 ]. It would also go beyond the scope of this review to discuss in detail cancer-related animal studies that identified upstream regulators of AnxA2 expression or activity [ 176 , 177 , 178 ].…”
Section: Anxa2mentioning
confidence: 85%
“…Although data from p11 KO-mice often supports findings that AnxA2/p11-dependent plasmin generation is involved in tumour progression [ 115 , 116 , 121 ], it should be noted that p11 has plenty of other tumourigenic functions that appear rather unrelated to AnxA2 [ 174 , 175 ]. It would also go beyond the scope of this review to discuss in detail cancer-related animal studies that identified upstream regulators of AnxA2 expression or activity [ 176 , 177 , 178 ].…”
Section: Anxa2mentioning
confidence: 85%
“…The ANXA2 subunit helps to stabilize and anchor S100A10 to the plasma membrane, and AIIt activates plasminogen via tissue-type plasminogen activator (t-PA) and urokinase-type plasminogen activator (uPA). This in turn increases the production of plasmin, leading to the activation of metalloproteinases (MMPs) and the degradation of extracellular matrix (ECM) proteins, thereby promoting tumor progression and chemoresistance [31, 32]. Liu et al found that ovarian cancer proliferation and invasion can be suppressed by inhibiting ANXA2 via β-catenin/EMT [33].…”
Section: Discussionmentioning
confidence: 99%
“…Annexin A2 and S100A10 form a heterotetramer referred to as AIIt, which interacts with the tissue plasminogen activator (tPA). This leads to the production of plasmin, which results in ECM degradation, EMT, and angiogenesis [151,152]. In addition, S100A10 is able to promote MMPs, altogether provoking cell migration and invasion [153].…”
Section: S100 Proteins In Ovarian Cancermentioning
confidence: 99%